Description of the main aspects influencing Bombyx mori L. (Lepidoptera: Bombycidae) rearing - Torres, A. R.; Caballero, Beatriz; Ruiz, Adileidys (Cuban Journal of Agricultural Science, 2021)
Bombyx mori L. is one of the most important species for silk production internationally. Being a domesticated species, there are certain factors to be considered during its breeding. This paper discusses the influence of certain factors on silkworm rearing. Reference is made to B. mori breeds and their peculiarities regarding their productive characteristics. In addition, the effects of certain environmental factors are explained, as well as their interaction with food and diseases that affect silkworm. Regarding the latter, the main strategies used for fighting them are mentioned. The interaction of larvae, environment, food and diseases influence mainly on B. mori rearing. The success of this agribusiness is determined by the strict control over these factors. Keywords: silkworm, breeds, environment, pathologies